6S RNA modulates growth and antibiotic production in Streptomyces coelicolor - Mikulík, Karel; Bobek, Jan; Zídková, Jarmila; Felsberg, Jurgen (Applied microbiology and biotechnology, 2014)
The aim of this study was to contribute to clarifying the role of 6S RNA in the development and control of antibiotic biosynthesis in Streptomyces coelicolor. Due to the low energetic cost of gene silencing via 6S RNA, it is an easy and rapid means of down-regulating the expression of specific genes in response to signals from changes in the environment. The expression of 6S RNA in S. coelicolor is not constitutive, and its accumulation is adapted to changes in nutritional conditions. The 6S RNA of S. coelicolor is capable of interacting with RNA polymerase β β' subunits and is a template for the transcription of short pRNAs. Deletion of the ssrS gene from S. coelicolor affects the growth rate and causes changes in the expression of several pathway-specific genes involved in actinorhodin biosynthesis. The complementation of the ΔssrS strain with ssrS gene restored the wild-type levels of growth and actinorhodin production. We conclude that 6S RNA contributes to the optimization of cellular adaptation and is an important factor involved in the regulation of growth and expression of key genes for the biosynthesis of actinorhodin.
Keywords: testy genetické komplementace; nekódující RNA; Protein Binding; antibakteriální látky; delece genu; bakteriální RNA; DNA-Directed RNA Polymerases; vazba proteinů; DNA řízené RNA-polymerasy; Streptomyces coelicolor; RNA, Untranslated; RNA, Bacterial; Anti-Bacterial Agents; regulace genové exprese u bakterií; Gene Deletion; Genetic Complementation Test; Gene Expression Regulation, Bacterial